Effectiveness of Distribution of Baznas Microfinance Village Business Funds to Mustahiq: Opportunities and Challenges - Ahmad Fauzi Asshidqi; M. Nanang Febrianto; Zulfah Jannatul Karimah; Binti Nur Asiyah (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
This community service aims to analyze the effectiveness, opportunities, and challenges of the BAZNAS Microfinance Desa (BMD) Tulungagung fund distribution program in empowering vulnerable Micro, Small, and Medium Enterprises (MSMEs). The community service design applies an economic empowerment model, which focuses on building the capacity of individuals and groups through access to resources, training, and markets to achieve inclusive and sustainable economic self-sufficiency. The stages of this community service activity are problem identification, activity planning, implementation followed by the distribution of business funds to the Mustahiq Assistance Group, periodic monitoring and evaluation. The results of this study indicate that the distribution of funds through the Qardhul Hasan scheme (interest-free loans) is effective in addressing capital constraints and supporting the sustainability of partner businesses. This effectiveness is supported by the implementation of Maqasid al-Sharia, as manifested through spiritual mentoring and legal support for business. BMD not only provides capital but also builds a holistic mentoring ecosystem. The challenges faced by BMD include unsecured credit risk and partners' limited managerial capacity. The sustainability of the BMD program requires long-term strengthening to achieve the vision of transforming mustahiq into muzakki. Overall, this community service activity contributes to increasing business capacity, strengthening the MSME ecosystem in the Tulungagung area, and transforming mustahiq into muzakki, thereby implementing the BMD program's sustainability objectives.